Functional Capacity in Congenital Heart Disease: A Systematic Review and Meta-Analysis - Schaan,Camila Wohlgemuth (2017)
Abstract Background: Children and adolescents with congenital heart disease often have alterations in their exercise capacity that can be evaluated by various functional testing. Objective: To evaluate the functional capacity of children and adolescents with congenital heart disease (CHD) with systematic review and meta-analyses. Methods: The review included observational studies, data from the first evaluation of randomized clinical trials or observational follow-up periods after clinical trials which evaluated functional capacity by cardiopulmonary exercise test, stress testing, six-minute walk test or step test, in children and adolescents with CHD, aged between six and 18 years, and comparisons with healthy controls in the same age group. The quantitative assessment was performed by meta-analysis, by comparing the maximal oxygen consumption (VO2max) of children and adolescents with CHD and respective control groups. Results: Twenty-five of 2.683 studies identified in the search met the inclusion criteria. The VO2max measurement showed that patients with CHD have a decrease of 9.31 ml/Kg/min (95% CI. -12.48 to -6.13; I2, 94.3%, P for heterogeneity < 0.001) compared with the control group. The meta-analysis of the data of maximum heart rate (HR) reached during cardiopulmonary test and stress testing, retrieved from 18 studies, showed a HR value of -15.14 bpm (95% CI. -20.97 to -9.31; I2, 94.3%, P for heterogeneity < 0.001) compared with the control group. Conclusion: Children and adolescents with CHD have lower VO2max and HR compared to controls.